Endovascular repair of a complex giant infrarenal abdominal aortic aneurysm - Yoshida, Ricardo A. [UNESP]; Yoshida, Winston B. [UNESP]; Kolvenbach, Ralf; Jaldin, Rodrigo G. [UNESP]; Sobreira, Marcone L. [UNESP]; Hirga, Marcelo [UNESP] (SAGE Publications, 2015)
Giant aortic aneurysms (transverse diameter greater than 10.0 cm) are rare and open surgery is often the treatment of choice. We report an infrarenal saccular giant aortic aneurysm (measuring 25 cm in transverse diameter), which was treated with endovascular repair, with immediate technical success. No similar report of a giant infrarenal aortic aneurysm treated with an endovascular technique was found in the literature. High-risk patients could possibly benefit from the endovascular technique. Nevertheless, patient survival remains strongly influenced by comorbidities.
Keywords: Abdominal aorta; Aortic aneurysm; Endovascular procedure